Peningkataan Motorik Halus Anak Usia Dini Melalui Kegiatan Melipat Kertas Origami - Febriyeni; Ismet, Syahrul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study was motivated by the low fine motor skills of children aged 3-4 years at PAUD Cahaya Ibu in Sawahlunto City. The children appeared to struggle with activities requiring small muscle coordination, such as folding paper, resulting in untidy outcomes and requiring significant assistance from teachers. This research employed Classroom Action Research (CAR) involving 10 children, consisting of 5 boys and 5 girls. The research procedure was conducted in 2 cycles, with each cycle comprising planning, action implementation, observation, and reflection stages. Data were collected through observation, interviews, and documentation techniques and then analyzed descriptively. The research results showed a significant improvement in children's fine motor skills, with 35% of children meeting the